2020
DOI: 10.1177/2156759x20976374
|View full text |Cite
|
Sign up to set email alerts
|

School Counselors’ Self-Efficacy in Knowledge of the College Process

Abstract: This study examined the self-efficacy of school counselors’ college knowledge in the college process. Exploratory factor analysis revealed five characteristic factors: school counselors’ knowledge related to the college application process, systems advocacy, direct services with disadvantaged populations, direct service with special populations, and coordination of college access events. Hierarchical regression analyses revealed that both school counselors’ individual characteristics (e.g., years of experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
3
0
2
Order By: Relevance
“…This finding confirmed by a previous research in which novice counselors sensed confident in meeting the counseling needs of gifted students (Edwin & Fisher, 2023). Nice et al (2020) also indicated that school counselors feel confident in dealing with students' challenges after starting to work with students, without lacking more experience. It may be speculated that novice counselors were more eager than senior counselors to serve gifted students.…”
Section: Discussionsupporting
confidence: 87%
“…This finding confirmed by a previous research in which novice counselors sensed confident in meeting the counseling needs of gifted students (Edwin & Fisher, 2023). Nice et al (2020) also indicated that school counselors feel confident in dealing with students' challenges after starting to work with students, without lacking more experience. It may be speculated that novice counselors were more eager than senior counselors to serve gifted students.…”
Section: Discussionsupporting
confidence: 87%
“…2) руководство пользователя для приложения. В работе M. L. Nice с коллегами [28] обоснован опросник эффективности деятельности школьного консультанта, предполагающий оценку знаний, умений, способов, необходимых для эффективного сопровождения обучающихся при переходе в колледж.…”
Section: обзор литературыunclassified
“…Развивая положения исследований T. H. Retnowati с соавторами [27], M. L. Nice, M. Joseph, J. B. Kolbert, D. N. Hilts, L. M. Crothers, K. Kratsa [28], E. Cleveland, J. Hartline [9], занимавшихся вопросами разработки диагностического инструментария оценки эффективности школьного консультанта, нами определен доступный для использования в школьной образовательной практике диагностический инструментарий (чек-листы, опросники), позволяющий осуществить разностороннюю оценку эффективности деятельности классного руководителя.…”
Section: обсуждение результатовunclassified
“…If school counselors do not feel confident in their abilities to promote college knowledge to future FGCS, students will not believe they are adequately prepared to make decisions regarding their postsecondary path. In a survey that included 19,193 high school, middle, and junior high school counselors, results indicated they have a higher level of self-efficacy when increasing students' college knowledge, overall, but have a lower self-efficacy level when working with marginalized populations, which includes first-generation college students (Nice et al, 2020). Therefore, this hesitancy is leaving future FGCS with a deficit of college knowledge that is inadequate for making confident decisions regarding post-secondary endeavors.…”
Section: ) Asca Expectationsmentioning
confidence: 99%
“…As discussed in previous sections, the ASCA model contains a clear outline of the roles and responsibilities of a counselor in relation to increasing college knowledge. Although the ASCA model is meant to guide school counselors in their work, the self-efficacy level is not as high when it comes to working with specific populations (Nice et al, 2020). With that, Dockery and McKelvey (2013) noted several concerns school counselors had related to their training and preparation in working with high school students in enrolling and being successful at higher education institutions.…”
Section: ) Asca Model Expectationsmentioning
confidence: 99%